An institution in search of excellence: lessons learnt - Fatimah, H.; Halimah, A. (Shannon Research Press, 2005)
This is a report of the strategies adopted by the University of Malaya (UM), Malaysia, to address the issues and complexities involved in its search for excellence in teaching and learning, research and service. The story is told how the university sought accreditation through the International Standards Organisation (ISO) and how by uniting their heartbeats to breathe as one provides a platform for some individuals to rise to the occasion thereby adding strength to the team's struggle. The paper concludes that obtaining ISO certification is only a means to an end and, although the initiative towards change may have come from the top management of the university, any attempt to bring about change, requires that the parties involved have to become the change agents themselves.